Art to Come : Histories of Contemporary Art - Smith, Terry (Terry E.) (Book collections on Project MUSE., 2019)
In 'Art to Come' Terry Smith-who is widely recognized as one of the world's leading historians and theorists of contemporary art-traces the emergence of contemporary art and further develops his concept of contemporaneity. Smith shows that embracing contemporaneity as both a historical concept and a condition of the globalized world allows us to grasp how contemporary art exists in a fluid space of increasing interdependencies, multiple contemporaneous modernities, and persistent inequalities. Throughout these essays, Smith offers systematic proposals for writing contemporary art's histories while assessing how curators, critics, philosophers, artists, and art historians are currently doing so. Among other topics, Smith examines the intersection of architecture with other visual arts, Chinese art since the Cultural Revolution, how philosophers are theorizing concepts associated with the contemporary, Australian Indigenous art, and the current state of art history.